DETERMINAN MINAT PELAKU USAHA PRODUK MAKANAN KEMASAN MENGURUS SERTIFIKASI HALAL DI KOTA BANDA ACEH - Zahrina Keumala Zahusa; Ikhsan Ikhsan (JURNAL ILMIAH MAHASISWA EKONOMI ISLAM, 2021)
In Constitution no. 33 of 2014 which explains determination halal certification, it is stated that “halal certification must exist in every product” in its implementation, or in reality, There are still a lot things that don’t have a certification halal. The goal this studie it’s for look at the effects of religiosity in two ways: partially and simultaneously, halal certification procedures, and halal certification regulations on the interest in halal certification in packaged food product businesses in Banda Aceh City. Based on 78 questionnaires distributed to proportionate stratified random data sampling technique was used to collect all data from respondent, which was then uses analysis mutiple linear regression models, show result that religiosity, Halal Certification Procedures, and Certification Regulations simultaneously influenced interest in Halal Certification in packaged food product business actors. In Banda Aceh. And partially then this variable starts religiosity, Certification Halal Procedures, Certification Regulations own a positive and has a significiant effect on Halal Certification Interests in packaged food product business actors in Banda Aceh City.